Pendidikan Karakter Berbasis Islam pada Anak Autis - Khaerudin, Khaerudin; Kholifah, Elisa Putri; Indriyani, Fauziyah; Muttaqin, Dafiq Nur; Nurhidayati, Risqina Putri; Pradhiyatya, Alvathera Bima (MASALIQ, 2021)
The number of children with autism in Indonesia is no longer in small numbers, in this case it is not only the medical side or the psychological side that needs to be considered, but it is also necessary to pay attention to the education side too, maybe many think that being put into special schools or special schools is enough. enough to guide autistic children even though in reality it is not enough to cover the fate of children's character education, especially in their Islamic character. Looking at the behavior of children with autism, they hurt themselves more, besides that, distrust appears in their souls and will also behave more aggressively than normal children in general. When viewed from the side of character education, character education will be very helpful in terms of giving direction to these children to become more independent individuals and beneficial to others in accordance with the grace that Allah SWT has given, therefore it needs serious direction and guidance because Teaching children who have privileges certainly requires special methods and strategies, therefore this needs to be considered further.